2023
DOI: 10.1126/science.abn9257
|View full text |Cite
|
Sign up to set email alerts
|

Taurine deficiency as a driver of aging

Abstract: Aging is associated with changes in circulating levels of various molecules, some of which remain undefined. We find that concentrations of circulating taurine decline with aging in mice, monkeys, and humans. A reversal of this decline through taurine supplementation increased the health span (the period of healthy living) and life span in mice and health span in monkeys. Mechanistically, taurine reduced cellular senescence, protected against telomerase deficiency, suppressed mitochondrial dysfunction, decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 124 publications
3
55
0
Order By: Relevance
“…Senescent cells secrete a range of molecules known as SASPs, including chemokines, growth factors, matrix-degrading proteases, and pro-inflammatory cytokines. 33–35 SASPs contribute significantly to skin photoaging. 6 Senescent cells induced by UV express enzymes associated with ECM remodeling, particularly MMP1/3/9.…”
Section: Discussionmentioning
confidence: 99%
“…Senescent cells secrete a range of molecules known as SASPs, including chemokines, growth factors, matrix-degrading proteases, and pro-inflammatory cytokines. 33–35 SASPs contribute significantly to skin photoaging. 6 Senescent cells induced by UV express enzymes associated with ECM remodeling, particularly MMP1/3/9.…”
Section: Discussionmentioning
confidence: 99%
“…S2). The mRNA of human TAUT was found to be widely expressed in various human tissues, such as the lungs, kidneys, and liver, due to the recognized role of taurine, an endogenous substrate of TAUT, as an organic osmolyte [41, 42]. In contrast, ASBT mRNA was exclusively detected in the human ileum and kidney [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…[ 31–33 ] In previous studies, taurine has been found to possess significant antisenescence and anti‐inflammatory regulatory effects. [ 34–37 ] The antioxidant properties of taurine have been confirmed by many findings, including direct and indirect scavenging of reactive oxygen species (ROS). [ 38–41 ] Taurine exerts its antioxidant effects by inhibiting ROS generation and elevating antioxidant enzyme activities, as ROS production is diminished by increased antioxidase activities.…”
Section: Introductionmentioning
confidence: 99%